Experiment Investigation on the Effect of Oxygen Percentage on Combustion Characteristics of Waste Cooking Oil Biodiesel - Sasongko, Mega Nur; Wijayanti, Widya (International Journal of Integrated Engineering, 2021)
The main problem in making biodiesel is the cost of raw materials, the scarcity of raw materials for vegetable oils and the process of converting biomass to biodiesel. The use of waste cooking oil to produce biodiesel is an effective method to reduce raw material costs. This study aims to determine the effect of the percentage of oxygen on the combustion characteristics of premixed spray flame of biodiesel waste cooking oil. The combustion characteristics included the dimension of flame, lift-off, visualization of the flame and flame stability which was indicated by the percentage of oxygen on the oxidizer when extinction. The combustion of diesel spray flame was also measured for comparison purpose. In the experiment, the percentage of oxygen in the oxidizer stream was varied from 50% to 100%. The total flow rate of oxidizer was also varied from 7 LPM to 10 LPM. Whereas the flow rate of waste cooking oil was kept constant at 14 ml/min. The spray of biodiesel was carried out using a water atomizing nozzle with a diameter tip of 0.5 mm. The results showed that the height and width of the spray flame decreased with increasing variation in oxygen percentage. The height and width of the diesel flame is greater than that of waste cooking oil biodiesel. The height of biodiesel spray flame tends to decrease with increasing percentage of oxygen. The percentage of blue flame color increases with the increasing percentage of oxygen in biodiesel fuel while the flame of the diesel spray becomes yellow. For the stability of the cooking oil flame, the greater oxidizing flow rate results in a smaller percentage of oxygen that needed when extinction